Mô hình TPACK trong dạy học hòa âm jazz tại Việt Nam: Từ lí thuyết đến thực tiễn - Nguyễn Mai Kiên, Nguyễn Mai Kiên; Phạm Tú Hương, Phạm Tú Hương (Tạp chí Giáo dục, 2026)
In the context of the profound digital transformation in education, integrating technology into Jazz harmony pedagogy in Vietnam has become an imperative, not only to keep pace with global trends but also to address the inherent challenges of traditional teaching methods. This paper focuses on analyzing and addressing the core conflict in Jazz harmony instruction in Vietnam: the gap between traditional, theory-heavy teaching methods and the demands for application and creativity in practical Jazz improvisation. This situation results in a scenario where students may master the rules but struggle during practical performance, lacking flexible application skills. To address this situation, this study proposes the application of the Technological Pedagogical Content Knowledge (TPACK) framework as its theoretical foundation. The TPACK model emphasizes the seamless integration of three core components: content, pedagogy, and technology. Based on this framework, the study constructs a practical teaching model that operates within a technological ecosystem of specialized music learning and notation software. The study also proposes its implementation through a specific fourstep process. The objective of this research is to shift learning from passive to active, bridge the gap between theory and practice, and thereby develop students’ comprehensive competencies to meet the demands of the contemporary music scene.